Comparing Reading Comprehension Performance of Indonesian and Malaysian Junior Secondary Students: A Quantitative Comparative Study - Al Ghaniy Ra'uf; Sudar; Abdul Ngafif; Ameerul Husni bin Khairol Azman (Faculty of Education and Teacher Training of UIN Palopo, 2026)
While extensive research has explored literacy policies in Southeast Asia, empirical cross-national comparisons of reading achievement at the junior secondary level remain scarce. This study addresses this gap by comparing the reading comprehension proficiency of eighth-grade students in Indonesia and Malaysia. Employing a comparative quantitative design, the research was conducted at SMP Negeri 6 Purworejo, Indonesia, and SMA Al-Falah Batu Talam, Malaysia, during the 2024/2025 academic year (N = 68). Data were elicited through a validated 25-item multiple-choice test focusing on descriptive and report texts. Independent samples t-test results revealed a significant performance disparity (t(66) = 4.38, p < .001), with Indonesian students (M = 89.53, SD = 11.73) significantly outperforming their Malaysian counterparts (M = 70.24, SD = 22.74). The calculation of Cohen’s d (1.066) further confirmed a large effect size. These findings suggest that higher proficiency in the Indonesian cohort is associated with standardized literacy practices and teacher-led